Evaluation of femtosecond laser-assisted anterior capsulotomy in the presence of ophthalmic viscoelastic devices (OVDs) - Mansoor, Hassan (2021)
The introduction of femtosecond laser-assisted cataract surgery is an alternative approach to conventional cataract surgery. Our study aimed to determine the effectiveness of femtosecond laser-assisted capsulotomy in the presence of different ophthalmic viscoelastic devices (OVDs) in the anterior chamber. Fresh porcine eyes (n = 96) underwent LDV Z8-assisted anterior capsulotomy, either in the presence of an OVD (Viscoat, Provisc, Healon, Healon GV or HPMC) or without, using 90% and 150% energies respectively. Following that, the capsule circularity, tag's arc-length, tag-length, tag-area and rupture strength (mN) of the residual capsular bag were evaluated. We found that increasing energy from 90 to 150% across the OVD sub-groups improved the studied capsulotomy parameters. Amongst the 90% energy sub-groups, the circularity and tag-parameters were worse with Viscoat and Healon GV, which have higher refractive index and viscosity compared to the aqueous humour. Using 150% energy, Healon GV showed a significantly worse total arc-length (p = 0.01), total tag-length (p = 0.03) and total tag-area (p = 0.05) compared to the control group. We concluded that; an OVD with a refractive index similar to aqueous humour and lower viscosity, such as Healon or Provisc, as well as a higher energy setting, are recommended, to enhance the efficacy of laser capsulotomy.